Cover Feature: Importance of Electron Mediator Transparency: Photocatalytic Hydrogen Production from Polyoxometalate using Dye‐double‐layered Photocatalysts (ChemCatChem 4/2023). Issue 4 (20th February 2023) - Yoshimura, Nobutaka; Tomita, Osamu; Abe, Ryu; Yoshida, Masaki; Kobayashi, Atsushi
Abstract : The Cover Feature shows the photocatalytic hydrogen production by dual Ru(II)‐dye sensitized layered niobate oxide with intercalated Pt cocatalyst in the presence of redox‐reversible M ‐substituted polyoxometalate anions ( M ‐POM, M = V IV, Mn II ). In their Research Article, A. Kobayashi and co‐workers found that the photocatalytic activity is remarkably higher in Mn II ‐POM aq. than that in V IV ‐POM aq. despite their comparable redox potentials. Their experimental results suggest that the visible‐light transparency of surface‐immobilized M ‐POM is the key factor for the photocatalytic H2 production activity. More information can be found in the Research Article by A. Kobayashi and co‐workers .